2013
DOI: 10.1007/s10900-013-9781-y
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Offers Protection Against Obesity in Children of Recently Immigrated Latina Women

Abstract: Breastfeeding has been found to have a protective effect on subsequent development of obesity in childhood, particularly in white, non-Hispanic populations. The protective effect of nursing for more than 12 months in children of Latina women is less clear, which may be due to differences in levels of acculturation in previously studied populations. We evaluated the association between breastfeeding for 12 months or more and risk for obesity in a cohort of children of recently immigrated relatively unacculturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 18 publications
2
30
0
3
Order By: Relevance
“…Our study found that leukocyte telomere length at age 4 and 5 years was associated with obesity at 9 years, as was reduced maternal education level after adjustment for known risk factors for this cohort . Of the subset of children who were obese at 9 years, the prevalence of chronic obesity was 76%, possibly indicating increased risk for future metabolic disease development in this subset.…”
Section: Discussionmentioning
confidence: 53%
“…Our study found that leukocyte telomere length at age 4 and 5 years was associated with obesity at 9 years, as was reduced maternal education level after adjustment for known risk factors for this cohort . Of the subset of children who were obese at 9 years, the prevalence of chronic obesity was 76%, possibly indicating increased risk for future metabolic disease development in this subset.…”
Section: Discussionmentioning
confidence: 53%
“…Hispanic children in particular have persistently had higher obesity prevalence rates (14.8%) compared to black infants (8.7%) and white infants (8.4%) [5]. Verstraete et al [6] found that infants of recently immigrated Latina women who were breastfed up to 1 year of age had a decreased risk of obesity at 3 years of age. Additionally, a study conducted in Brazil found that breastfeeding duration positively impacts intelligence quotient (IQ), years of schooling, and income at 30 years of age [7].…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding is also associated with a 9% reduction in asthma and a 68% reduction in dental malocclusion. Verstraete and colleagues [6] found that, for recently immigrated Latina mothers, breastfeeding for a year or more is associated with a healthier infant weight, specifically a decreased weight percentile for age, body mass index percentile and z -score for age, and waist circumference below the 90th percentile. Results also showed that breastfeeding for a year or longer was associated with a decreased risk of obesity and persisted after controlling for maternal BMI, marital status, education, country of origin, age, years of living in the United States, and child's birthweight.…”
Section: Introductionmentioning
confidence: 99%
“…9 der 17 eingeschlossenen Studien untersuchen den Einfluss der Akkulturation auf das Stillverhalten der Frauen mit Migrationshintergrund [2, 5, 6, 13, 14, [16][17][18][19]. Von den 4 Studien aus den USA, die den Zusammenhang zwischen Akkulturationsstatus und Stillverhalten von Latinas untersuchten [16][17][18][19], konnten 3 Studien einen stillhemmenden Einfluss der zunehmenden Akkulturation auf das Stillverhalten der Latinas zeigen [17][18][19]. Eine der 4 Studien [17] hat zusätzlich keinen negativen Effekt der Aufenthaltsdauer auf das Stillverhalten gezeigt und eine [16] fand keine Assoziation zwischen zunehmender Akkulturation und Stilldauer.…”
Section: Akkulturation Und Stillverhaltenunclassified
“…Von den 4 Studien aus den USA, die den Zusammenhang zwischen Akkulturationsstatus und Stillverhalten von Latinas untersuchten [16][17][18][19], konnten 3 Studien einen stillhemmenden Einfluss der zunehmenden Akkulturation auf das Stillverhalten der Latinas zeigen [17][18][19]. Eine der 4 Studien [17] hat zusätzlich keinen negativen Effekt der Aufenthaltsdauer auf das Stillverhalten gezeigt und eine [16] fand keine Assoziation zwischen zunehmender Akkulturation und Stilldauer. Vier Arbeitsgruppen [2, 5, 6, 14] berichteten über einen negativen Einfluss der Akkulturation auf das Stillverhalten der Frauen mit Migrationshintergrund, während nur eine [13] keinen stillhemmenden Effekt fand.…”
Section: Akkulturation Und Stillverhaltenunclassified